2009
DOI: 10.1603/022.038.0325
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence ofTrichosirocalus horridus(Coleoptera: Curculionidae) on NativeCirsium altissimumVersus ExoticC. vulgarein North American Tallgrass Prairie

Abstract: Postrelease studies can provide data with which to evaluate expectations based on prerelease tests of biological control insects. In 2004, we observed Trichosirocalus horridus Panzer (Coleoptera: Curculionidae), the rosette weevil introduced into North America against Eurasian thistles, feeding on native tall thistle, Cirsium altissimum L. Spreng., in tallgrass prairie. In this study, we examined the rosette weevil's use of tall thistle, compared with its use of the co-occurring exotic bull thistle, C. vulgare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Both richness and abundance of thistle specialist and generalist insect herbivores on C. vulgare were comparable to the native C. altissimum (Takahashi et al 2009). The phenological synchrony of C. vulgare with C. altissimum has been hypothesized to facilitate herbivore transfer (Jackson 1998;Louda and Rand 2002;Andersen and Louda 2008).…”
Section: Effects Of Insect Herbivorymentioning
confidence: 78%
See 2 more Smart Citations
“…Both richness and abundance of thistle specialist and generalist insect herbivores on C. vulgare were comparable to the native C. altissimum (Takahashi et al 2009). The phenological synchrony of C. vulgare with C. altissimum has been hypothesized to facilitate herbivore transfer (Jackson 1998;Louda and Rand 2002;Andersen and Louda 2008).…”
Section: Effects Of Insect Herbivorymentioning
confidence: 78%
“…Although C. vulgare is sparse in eastern Nebraska (Andersen and Louda 2008), it is highly invasive in other regions of the USA (USDA 2009), as well as in Australia (Medd 1981) and New Zealand (Johnson 1982). In eastern Nebraska, C. vulgare is a host plant for many indigenous insect herbivore species (Takahashi et al 2009); and, we found that feeding by these insects on C. vulgare significantly reduced both growth (Figure 2) and seed matured (Figure 3) in its final, flowering year. Contrary to the classic assumption that competition from native plants provides strongest resistance to invasion by introduced weeds, a recent meta-analysis (Levine et al 2004) found that herbivory by native insects can be as important as competition in resisting invasion by introduced plants.…”
Section: Effects Of Insect Herbivorymentioning
confidence: 99%
See 1 more Smart Citation
“…These occurrences are the first reports of T. horridus feeding to any degree on C. carolinianum, C. horridulum, or C. muticum in the US and only the second record of non-target feeding on C. altissimum (Piper and Coombs 2004;Takahashi, Louda, Miller, and O'Brien 2009). Furthermore, the infested populations of C. altissimum in Sevier Co. and C. discolor in Blount Co. are both within the borders of the Great Smoky Mountains National Park (GRSM).…”
Section: Biocontrol Science and Technology 995mentioning
confidence: 80%
“…For example, timed observations conducted throughout the growing season at two sites in Lancaster County, Nebraska, revealed that 97% of the individuals identified on C. vulgare were native species (see ESM 1 in the supporting information). The primary non-native insect herbivore on C. vulgare in eastern Nebraska is Trichosirocalus horridus (ESM 1); specifically, in a survey of 13 sites in Lancaster County, adult T. horridus were found in fewer than 10% of C. vulgare shoots (Takahashi et al 2009). …”
Section: Natural History Contextmentioning
confidence: 99%